Case Report: Acute polymorphic psychosis and NMDA-R IgG antibodies in serum: a follow-up case study - von Zedtwitz, Katharina; Weiser, Judith; Dressle, Raphael J.; Maier, Simon J.; Feige, Bernd; Nickel, Kathrin; Venhoff, Nils; Domschke, Katharina; Brumberg, Joachim; Rauer, Sebastian; Tebartz van Elst, Ludger; Hannibal, Luciana; et al. (Frontiers in Immunology, 2025)
IntroductionAnti-N-methyl-D-aspartate receptor (NMDA-R) encephalitis is a neuropsychiatric disorder with additional psychiatric features caused by NMDA-R immunoglobulin G (IgG) antibodies in cerebrospinal fluid (CSF). This report presents the follow-up of a patient in whom we assumed mild NMDA-R encephalitis in the first psychotic episode.Case studyA patient with a prior episode of an acute polymorphic psychotic syndrome relapsed five and a half years later following a severe COVID-19 infection. Serum NMDA-R antibodies were again detected with a titer of max. 1:320 using fixed-cell-based assays, but conventional magnetic resonance imaging (MRI), electroencephalography (EEG), and CSF findings were largely normal. NMDA-R antibody levels in serum decreased to 1:80 after approximately one month without immunotherapy. [18F]fluorodeoxyglucose positron emission tomography (FDG-PET) still revealed pronounced metabolism of the association cortices (clearly more pronounced in the first episode with an encephalitis-like pattern at that time). Advanced MRI analyses including diffusion microstructure imaging (DMI) showed frontal and thalamic microstructural alterations compatible with edematization (but also far less accentuated than in the first episode). Further advanced antibody tests of CSF (approx. 1 month after symptom onset) using a live-cell-based and different tissue-based assays were negative for NMDA-R IgG antibodies. Research mass spectrometry of the CSF identified neurotransmitter-precursor shortages, increased turnover of tryptophan into quinolinic acid, and low-glucose/lactate levels. Immunotherapy (performed after the initial assumption of an autoimmune cause) with steroids led to clinical improvement of residual symptoms. After approximately three months, NMDA-R IgG serum antibodies were no longer detectable; however, FDG-PET/DMI follow-up revealed no relevant changes.DiscussionThe international consensus criteria for a probable/definite diagnosis of NMDA-R encephalitis or autoimmune psychosis were not fulfilled, especially as no NMDA-R IgG antibodies were identified in CSF using different antibody assays and EEG/CSF routine findings were inconspicuous. NMDA-R encephalitis was therefore not diagnosed (as initially suspected). Independent of the NMDA-R IgG antibodies, there were possible signs of an autoimmune process. For a better understanding of similar patients, multimodal diagnostic approaches including complementary antibody tests could be promising.